Greenland Ice Surface Temperature, Surface Albedo, and Water Vapor from MODIS Comparison Tool - Felikson, Denis; Simon, Erika; Hall, Dorothy K.; DiGirolamo, Nicolo; Snitzer, Elliot (Ghub, 2021)
This tool comparesGreenland Ice Sheet surface temperature from a model against observations. The observations are compiled in a multilayer data product called Multilayer Greenland Ice Surface Temperature, Surface Albedo, and Water Vapor from MODIS, Version 1 (MODGRNLD; https://nsidc.org/data/MODGRNLD ). This dataset includes both monthly and daily resolutions. Currently, this tool uses modeled ice sheet surface temperature from the Modern-Era Retrospective analysis for Research and Applications, Version 2 (MERRA-2; https://gmao.gsfc.nasa.gov/reanalysis/MERRA-2 ). An example of this modeled data is provided with the tool at monthly resolution for January, 2015. This tool interpolates MERRA-2 data to the higher-resolution MODGRNLD observations, creates a map plot and a histogram of the differences in ice sheet surface temperature. The user is able to download both plots. Files downloaded by this tool are netCDF4(.nc4) files. They are stored in the /data directory under the path /data/groups/ghub/tools/modgrnld. Depending on whether the files are from the MODGRNLD or MERRA-2 datasets, they will be stored in the subdirectory MERR-2 or MODGRNLD. Files used for Albedo or Water Vapor data analyses will be deleted from /data after they are used to provide the proper outputs. This is due to the large amount of space they use in local storage. This tools is published in an interactive notebook on Ghub. References Hall, D., Cullather, R., DiGirolamo, N., Comiso, J., Medley, B., & Nowicki, S. (2018). A Multilayer Surface Temperature, Surface Albedo, and Water Vapor Product of Greenland from MODIS. Remote Sensing, 10(4), 555–17. http://doi.org/10.3390/rs10040555